2008
DOI: 10.1111/j.1741-3729.2008.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Emotion Regulation and Sibling Relationship Quality: The More Fun With Sisters and Brothers Program*

Abstract: We examined the role of emotion regulation (ER) in improving sibling relationship quality (SRQ) by evaluating the More Fun With Sisters and Brothers Program where 4-to 8-year-old siblings from 95 families were taught emotional and social competencies. Parents reported on SRQ and ER, and sibling interactions were observed in homes. SRQ and ER improved for program participants (n ¼ 55) in comparison to those in a wait list condition (n ¼ 40). Children participating in the program needed less parental direction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 36 publications
(40 reference statements)
3
92
1
7
Order By: Relevance
“…However, given that we observe an association over and above the effects of multiple family risk factors, our findings argue for the development of interventions specifically designed to target sibling bullying. Existing programs that target the sibling relationship more broadly 46,47 should be systematically evaluated to determine whether they lead to a reduction in sibling bullying and psychological harm.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…However, given that we observe an association over and above the effects of multiple family risk factors, our findings argue for the development of interventions specifically designed to target sibling bullying. Existing programs that target the sibling relationship more broadly 46,47 should be systematically evaluated to determine whether they lead to a reduction in sibling bullying and psychological harm.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…The vast majority of sibling research has focused on relationships in childhood, sibling attachments, rivalry, birth-order, and other related topics (e.g., Dunn, 1983;Furman & Buhrmester, 1985;Kennedy & Kramer, 2008;Stocker, Dunn, & Plomin, 1989). More recently, research has been conducted on elderly siblings (Bedford, 1989b;Schulman, 1999) and on sibling relations in late adulthood (Bedford, 1998c).…”
mentioning
confidence: 99%
“…For example, Brody et al(1999) found, in a sample of 9-to 12-year-old African-American youth, that higher self-regulation was related to more harmony and less conflict in the sibling relationship. Similarly, an intervention that promoted emotion regulation skills in sibling dyads between 4 and 8 years of age led to more positive sibling relationships (Kennedy & Kramer, 2008). Thus, in the current study, older siblings' inability to regulate their jealousy within the context of triadic interactions may be illustrative of less-developed emotion regulation skills that persist over time and predict subsequent sibling conflict.…”
Section: Children's Behaviour During Mother and Father Sessionsmentioning
confidence: 89%
“…We found that older siblings' jealous reactions in response to their fathers' interactions with their younger siblings independently predicted sibling relationship functioning above the effect of the child's jealousy with mother. Children learn to regulate their emotions within the context of the sibling relationship (Bedford & Volling, 2004;Brody, Stoneman, Smith, & Gibson, 1999;Kennedy & Kramer, 2008). For example, Brody et al(1999) found, in a sample of 9-to 12-year-old African-American youth, that higher self-regulation was related to more harmony and less conflict in the sibling relationship.…”
Section: Children's Behaviour During Mother and Father Sessionsmentioning
confidence: 97%